Comparison of the implementation of human papillomavirus and hepatitis B vaccination programs in the United States: Implications for future vaccines. Issue 5 (29th January 2020) - Constable, Catherine; Caplan, Arthur
Abstract: Vaccines for two viruses which cause cancer, human papillomavirus (HPV) and hepatitis B virus (HBV), are recommended for all children in the United States. Numerous parallels exist between the two vaccines in addition to their roles in cancer prevention, including transmission through sexual contact, multiple doses needed for series completion, and vaccine administration in adolescence for HPV and in the initial phase of the HBV vaccination program. All of these factors were viewed as potential barriers to achieving high rates of coverage, yet the ultimate success of the HBV vaccination program led to predictions that similarly high rates of coverage could be achieved for the HPV vaccine. However, currently, only the recommendation for HBV vaccination is supported by mandates for school entry in most states. Uptake of the HPV vaccine has lagged far behind U.S. goals for public health promotion. The aim of this paper is to examine factors which may account for the divergent pathways of the two vaccines. Four main factors are identified: logistical challenges of vaccine administration, attitudes of parents and healthcare providers, safety concerns, and cost. For each factor examined, recommendations are offered to confront similar barriers likely to arise for future vaccines. The authors conclude that gender-neutral state mandates coupled with school-located vaccination programs, stronger gender-neutral messaging from pharmaceutical companies and healthcare providers, and younger age of vaccine administration, if approved, present the most promising approaches to improving uptake of the HPV vaccine, and similar vaccines down the road.